The Role of the Medical Committee in Efforts to Improve the Quality of Services at Batu Bara Regional General Hospital - Okto, Okto Hebron Purba (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
The medical committee plays an important role in the hospital quality management system, especially in ensuring the professionalism of medical personnel, implementing clinical audits, and formulating service policies. However, the implementation of the role of the medical committee in regional hospitals often faces various structural and operational challenges. This study aims to analyze in depth how the medical committee plays a role in improving the quality of service at Batu Bara Regional Hospital and to identify the obstacles and strategies implemented. This research method uses a qualitative descriptive approach. Data were collected through in-depth interviews with the chairman and members of the medical committee, the hospital director, and medical personnel, documentation studies of policies and committee meeting reports, and direct observation of medical committee activities. The analysis was carried out using a thematic approach and source triangulation techniques to ensure the validity of the data. The results of the study indicate that the medical committee has carried out the functions of credentialing, medical audits, and formulating clinical policies with active involvement. However, the development of medical personnel and monitoring of clinical practices are still not optimal due to limited human resources, minimal ongoing training, and lack of information system integration. The medical committee is also a communication bridge between management and medical staff in clinical decision making. The role of the medical committee is very important in efforts to improve the quality of service in regional hospitals. Strong managerial support